Towards a Mayan Theory of Human Rights: Sacred Equilibria and the Consequences of Disrespect. Issue 4 (1st October 2016) - Ekern, Stener
ABSTRACT: Much discussion about human rights and indigenous peoples centres on the asymmetric relations between vulnerable groups and powerful states. This is so not least in Guatemala, where different Mayan-speaking groups live in the aftermath of a brutal war even as the country goes through a peace process underpinned by human rights considerations. However, the associated focus on relations and group rights comes at the cost of overlooking the reservoir of human experience that an indigenous society also is. This article discusses these asymmetric societal relations; however, the departure point is an investigation into how the K'iche' Mayas – the largest of the around twenty Mayan-speaking peoples of Guatemala – imagine good life and good government as compared to ideas about good government and ethical lives in a human rights perspective. Whereas human rights can be seen as a guarantor for the autonomy an individual human being needs, the key Mayan concepts in this regard are awas and nimanik, respectively "lack of respect" and "respect", for the sacred paths human and nature must follow in order to minimise sickness and pain. And the most important path is the path of the community. This article offers insight into the moral-political traditions of an indigenous people. The findings in this article suggest that less asymmetric relations can be ensured by building a human rights framework which incorporates concepts from local philosophies, in order to include all the elements a multicultural society must rely on to respect, protect and fulfil human rights.